Learning styles and approaches in Dentistry students and their relationship with academic performance in Pharmacology - Ariana Fernàndez Garcìa; Ileana Quiñones La Rosa; Rosa María Lam Díaz (Medisur)
Foundation: the learning styles and approaches allow us to know how the student faces this process and the way in which they process the information that must be assimilated. Objective: to identify the learning styles and approaches used by Dentistry students and their relationship with academic performance in the Pharmacology discipline. Methods: a descriptive-cross-sectional study, with a qualitative-quantitative approach, carried out from November 2021 to January 2022. The non-probabilistic sample consisted of 28 students (90.3%) in the second year of the Dentistry course taught at the Havana Dentistry Faculty. Two instruments were applied to the participants: the Honey and Alonso questionnaire on learning styles and the Approaches and Inventory of Student Study Skills questionnaire. The dimensions of academic performance were excellent, good, and regular. Results: the very high/high preference predominated in the theoretical style (67.86%) and the moderate preference in the reflective style (67.86%). A significant relationship was found between the number of very high/high preference learning styles and academic performance (p=0.044), and between the reflective style and academic performance (p=0.024). Also, a significant relationship was found between academic performance and the strategic learning approach (p=0.008) and the preference for the transmission of information (p=0.028). Conclusions: there are learning styles and approaches among students that are related to academic performance in Pharmacology; Aspects that should be considered for the improvement of the teaching process of this discipline in Dentistry are shown.